Manufacturing of Natural Fibre Reinforced Polymer Composites - Salit, Mohd Sapuan; Jawaid, Mohammad; Yusoff, Nukman Bin; Hoque, M. Enamul (Springer International Publishing : Imprint: Springer, 2015)
Natural fibers, derived from oil palm, sugar palm, bagasse, coir, banana stem, hemp, jute, sisal, kenaf, roselle, rice husk, betul nut husk, and cocoa pod, have been considered as reinforcing materials in polymer composites.  The unique properties of natural fibers including low cost, renewable, abundance, light weight, and less abrasive, suggest that they are suitable as semi-structural or non-structural engineering components.  Although research on natural fiber composites such as characterization, determination of properties, and design have been extensively carried out, these information are scattered and not easily accessible to non-specialists.  This book addresses such shortcoming and provides detailed accounts of natural fiber composites in terms of their physical and chemical properties, in relation to their applications in the manufacturing and engineering industries.  Chapters, written by experts in their respective fields, highlight the hidden values of natural fibers for all those who are interested in this exciting research discipline.